Ginsenoside Rg1 Ameliorates Rat Myocardial Ischemia-Reperfusion Injury by Modulating Energy Metabolism Pathways - Li, Lin; Pan, Chun-Shui; Yan, Li; Cui, Yuan-Chen; Liu, Yu-Ying; Mu, Hong-Na; He, Ke; Hu, Bai-He; Chang, Xin; Sun, Kai; Fan, Jing-Yu; Huang, Li; et al. (Frontiers in Physiology, 2018)
As a major ingredient of Radix ginseng, ginsenoside Rg1 (Rg1) has been increasingly recognized to benefit the heart condition, however, the rational behind the role is not fully understood. The present study was designed to investigate the protective effect of Rg1 on heart ischemia and reperfusion (I/R) injury, with focusing on the involvement of energy metabolism regulation in the underlying mechanism. Male Sprague-Dawley rats were subjected to 30 min of occlusion of left coronary anterior descending artery followed by reperfusion for 90 min. Rg1 (5 mg/kg/hour) was continuously administrated intravenously 30 min before occlusion until the end of reperfusion. Myocradial blood flow and heart function were monitored over the period of ischemia and reperfution. Myocardial infarct size, structure and apoptosis, energy metabolism and change in RhoA signaling pathway were evaluated 90 min after reperfusion. Binding of Rg1 to RhoA was assessed using Surface Plasmon Resonance. Rg1 prevented I/R-elicited insults in myocardium, including myocardial infarction and apoptosis, decreased myocardial blood flow and heart function, and alteration in myocardium structure. Rg1 restored the production of ATP in myocardium after I/R. Rg1 was able to bind to RhoA and down-regulate the activity of RhoA signaling pathway. These results indicated that Rg1 had protective potential against I/R-induced myocardial injury, which may be related to inhibiting myocardial apoptosis and modulating energy metabolism through binding to RhoA.